Seasonal effect on growth and simbiotic nitrogen fixation of different Azolla species - Ruschel, Alaides Puppin (Pesquisa Agropecuaria Brasileira, 2014)
A field trial was set up to study the seasonal effect on Azollagrowth, nitrogenase activity, simbiotic nitrogen fixation and P accumulation in an experiment repeated, monthly, June 1983 to August 1984 at Piracicaba, São Paulo, Brazil, being plants growing for 21 days. Five Azolla species (A. caroliniana, A. filiculoides, A. microphylla, A. mexicana and A. pinnata) were studied. There was a differential effect among species related to the time of the year for all parameters analysed. All species showed high yield and N-content in November (late spring). Maximum yield and total nitrogen over longer periods were shown by A. filiculoides and A. microphylla. The average ratio plant weight/ plant dry weight was above 25. Nitrogenase activity varied among species at winter time only. Maximum N-yields were 29, 29 and 37 kg/ha of N for A. filiculoides, A. mexicana, A. microphylla respectivelly, and for P accumulation 3.1, 3.6, and 4.6 kg/ha of P respectivelly. The poorest development for all species occurred during summer (January and February).